Developing Interactive Multimedia Software for English Learning - Y.G. Harto Pramono (Widya Mandala Surabaya Catholic University, 2012)
This paper describes a project aimed to develop interactive multimedia software which is pedagogically attractive and appropriate for Year 2 students of Elementary School to learn English. The software was developed using Macromedia Flash Professional 8. It presented one common theme: Animals. The learning activities provided in the software were carefully designed to help the students develop the four main skills for language acquisition – listening, speaking, reading, and writing – in an integrated way. To gain an optimal product, an evaluation by experts was conducted and the result of this evaluation was used as the basis for revising the software. In addition, a series of tryout by target users were conducted phase by phase. After each phase of the tryout was completed, the software was revised by addressing the results of the tryout to improve its quality. Based on the result of the final tryout, it can be concluded that the developed interactive multimedia software is pedagogically quite attractive and appropriate to help Year 2 students of elementary school learn English